The effects of gamma-irradiation on transformation temperatures of NiTi shape memory alloy - Zengin, Rasit (Elsevier Science Bv, 2010)
The influence of gamma-irradiation on transformation temperatures of NiTi shape memory alloy was investigated by differential scanning calorimetry. The austenite transformation temperatures shifted to higher temperatures after gamma-irradiation, whereas the martensite transformation temperatures shifted to lower temperatures. The equilibrium temperature, T(o) between the martensitic and parent phases increases with increasing irradiation dose. The Gibbs free energy values, Delta G(P -> M) for the transformation from parent phase to martensite phase were determined and the value of AG(P -> M) increases with increasing irradiation dose up to 60 kGy. The mechanism of gamma-irradiation inducing the martensitic transformation is due to the displacements of atoms from their lattice sites produced by the accelerated gamma particles. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Shape memory alloy; Gamma-irradiation; Transformation temperatures; Gibbs free energy